A comparison between timed and IMU captured Nordic ski glide tests - Breitschädel, F.; Berre, V.; Andersen, R.; Stjernström, E. (Procedia Engineering, 2012)
An inertial measurement unit (IMU) with six degrees of freedom (three orthogonal accelerometers and three orthogonal rate gyroscopes) was used to calculate the acceleration loss as a function of position down the test slope. A traditional timed glide test was performed at the same time. The results from both test methods were compared. To increase the accuracy of the sensor system, two speed sensors were installed at known positions. The gradient of the track was measured and utilized by the sensor system to correct measurement errors. A mathematical model, developed by Apertus AS (Asker, Norway) was used to estimate the snow friction coefficient based on the acceleration loss. The results from the IMU sensor provided more information, including peak acceleration, maximum speed, time required to reach maximum speed, and speed loss, which can easily be seen. The use of IMU sensors in gliding tests may prove useful to differ between skis (dµ ~ 0.01). We conclude that in order to detect the minute differences distinguishing the best skis (dµ ~ 0.001), sensors with an even higher degree of sensitivity than those tested in this experiment should be used.